(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Literature has become an important element in English language learning because it offers authentic language, rich vocabulary, and meaningful contexts. This article explores how literary texts support the development of reading, writing, speaking, listening, and cultural awareness. It also reviews modern methods for using literature in the classroom, including reader-response activities, task-based learning, extensive reading, and drama techniques. Although challenges such as complex language and cultural differences exist, careful text selection and teacher support help overcome them. Overall, literature serves as an effective tool for improving communicative competence and learner motivation.